Evolution of exocrine chemical defense in leaf beetles (Coleoptera: Chrysomelidae) - Pasteels, Jacques M.; Rahier, Martine; Braekman, J. C.; Daloze, D.; Duffey, S. (My University, 1989)
In this review we speculate on possible scenarios for the evolution of the very high diversity in chemical compounds liberated by exocrine glands of adults Chrysomelidae. Shift in host plant affinities and subsequent adaptation of the beetles to the plant toxins strongly influence the nature of the beetles' chemical defense.
Keywords: Cardenolides; dipeptides; isoxazolinone glucoside; pyrrolizidine alkaloids; host plant influence; toxin sequestration